Characterisation of liquid oil from pyrolysis of waste tyre / Rusmi Alias and Atiqah Mohd Rafee - Alias, Rusmi; Mohd Rafee, Atiqah (Universiti Teknologi MARA, 2020)
The aim of this study is to characterise the liquid oil produced from pyrolysis of waste tyre. In this study, a series of experiment were carried out at various process temperature from 300 °C to 500 °C. The degradation study was carried out by using TGA, meanwhile the pyrolysis process was done using a fixed bed reactor. Liquid oil obtained from the pyrolysis was analysed using FTIR and GC-MS. The oil yield was found to decrease with increasing final pyrolysis temperature and the yield of the gas increased. The highest oil yield was 58.3 wt. %. For pyrolysis at 400 °C. The pyrolysis of waste tyre at atmospheric pressure commenced at about 340 °C and completed at 460 °C. An increase in the aromatic content of the oil was observed with increasing temperature. However, the aliphatic content decreased as the temperature increased from 300 °C to 500 °C. It was observed that the amount of aliphatic fraction in the oil decreased from 7.8 wt. % to 5.4 wt. %. In the meantime, the number of aromatic compounds increased from 37.4 wt. % to 51.2 wt. %. The main aromatic compounds were limonene, xylene, styrene, toluene, trimethylbenzene, ethylbenzene and benzene.